Application of Lagging Village Mapping And Pre-Prosperous Family Using Back Propagation Algorithm In Bathin III Ulu District Bungo District Jambi Province - -, Pariyadi; Prakasiwi, Degita Astari (SENATIK STT Adisutjipto, 2018)
Lagging villages are areas that are generally located in districts that are relatively underdeveloped and have relatively underdeveloped populations compared to other regions on a national scale. Batin III Ulu District Bungo has 9 (nine) villages which have promising space potential including abundant forest resources, natural tourism, agricultural land and plantations. Village development has not yet had an optimal impact and there are still disadvantaged families in each village in Bathin III Ulu Subdistrict. Development of application mapping of disadvantaged villages and underprivileged families in Bathin III Ulu Subdistrict, Bungo District, Jambi Province is a qualitative research that aims to support the government in accelerating the implementation of services for underdeveloped villages and underprivileged families. Automated learning stage to determine mapping of disadvantaged villages and underprivileged families through the application of Artificial Neural Network (ANN) as an adaptive system to model complex relationships between input and output to find patterns in the data and collaboration with Leaflet.Js as a library used for making thematic spatial maps that can emphasize priority objects to be addressed immediately. The application is built on a web-based basis so that users can easily access it anywhere and anytime as a reference in determining future development policies.